Liquid–liquid phase separation regulates gene expression in plants - Diyi Fu; Bochen Jiang (Agriculture Communications)
Liquid–liquid phase separation (LLPS) is recognized as a key process for the efficient organization of macromolecules, including numerous proteins and nucleic acids, within cells, facilitating the formation and function of various membraneless organelles. Growing evidence shows that environmental cues, including light, temperature, hormones, and pathogens, trigger the LLPS of phase-separating proteins with intrinsically disordered or multimerization regions, thereby modulating plant growth and development. Proteins involved in phase separation form distinct biomolecular condensates localized across subcellular compartments, from the nucleus to the cytoplasm and organelles. Here, we summarize the plant condensates assembled by LLPS, with a focus on those that regulate gene expression either directly or indirectly through mechanisms such as DNA epigenetics, transcription, mRNA methylation, and RNA metabolism. These findings underscore the potential of exploiting reversible protein phase separation for plant engineering to enhance crop yield and stress tolerance.